Robustly Optimal Monetary Policy in a Microfounded New Keynesian Model - Klaus Adam; Michael Woodford (University of Mannheim, Department of Economics, 2012)
We consider optimal monetary stabilization policy in a New Keynesian model with explicit microfoundations, when the central bank recognizes that private-sector expectations need not be precisely model-consistent, and wishes to choose a policy that will be as good as possible in the case of any beliefs close enough to model-consistency. We show how to characterize robustly optimal policy without restricting consideration a priori to a particular parametric family of candidate policy rules. We show that robustly optimal policy can be implemented through commitment to a target criterion involving only the paths of inflation and a suitably defined output gap, but that a concern for robustness requires greater resistance to surprise increases in inflation than would be considered optimal if one could count on the private sector to have "rational expectations".
urn:nbn:de:bsz:180-madoc-298635
Keywords: D81; D84; E52; 330; robust control; near-rational expectations; belief distortions; target criterion